A survey of medical education leaders’ perceptions of postgraduate medical education reform - Ovseiko, P; Jenkinson, C; Buchan, A (2014)
Background: Reform of postgraduate medical education and training (PGME) is of major interest to the medical profession and the public. Objective: To assess medical education leaders’ perceptions of PGME reform. Design: A cross-sectional anonymous online survey. Setting: All medical education leaders in England. Participants: 298 medical education leaders from eight leadership groups based on their contribution to the planning, financing, organisation, delivery, and regulation of medical education and training. Measurements: A survey instrument included 9 substantive questions, which were scored on five-point scales, as well as 7 questions regarding informed consent and socio-demographic characteristics. Results: 154 respondents completed the survey for a 52% response rate. 82 respondents also provided open-ended comments, but 15 did not grant permission to cite them. Most respondents perceived the reform policy and process negatively. Respondents from different leadership often held divergent policy preferences and disagreed with the government’s preferred future policy directions. Limitations: There may be a non-response bias as the overall response rate was 52% and four leadership groups had response rates <50%. There may be also a selection bias as there is no universally accepted definition of the population of medical education leaders and a measurement bias as our survey instrument has not been previously validated. Conclusions: We advocate a bottom-up debate among PGME stakeholders with a view to building a national consensus on future policy options.